Expression of endothelial-leukocyte adhesion molecule-1 in elicited late phase allergic reactions. - D Y Leung; J S Pober; R S Cotran (The Journal of Clinical Investigation, 1991)
To better understand the events involved in the local migration of inflammatory cells into sites of allergic reactions, we studied expression of the cytokine inducible endothelial cell (EC) neutrophil adhesion molecule, endothelial-leukocyte adhesion molecule (ELAM-1), in sequential skin biopsies from patients with respiratory allergy during the late phase reaction (LPR) between 20 min and until 24 h after intradermal allergen (ragweed or dust mites) injection. In 7 of 7 atopic patients but in only 1 of 4 apparently normal controls, allergen induced appearance of ELAM-1 on EC. ELAM-1 expression occurred concurrently with the development of inflammatory cell infiltrates by 3-4 h after intradermal injection. Saline injected sites in all subjects were negative. Skin organ cultures demonstrated that allergen could produce the same EC changes in vitro whether allergen was injected in vivo 20 min before culture or added during skin culture. These EC changes in organ culture were inhibited by the presence of combined anti-sera to both TNF-alpha and IL-1, but not by antisera to either cytokine alone. We conclude that EC activation occurs in elicited LPR and suggest that cytokine-induced EC activation may play a role in the migration of inflammatory cells into allergic skin reactions. Furthermore, resident cells in the skin rather than infiltrating leukocytes appear to be the source of the cytokines that mediate endothelial activation. Images